Interclonal variation in the performance of Daphnia-magna Straus in chronic bioassays - Soares, Amadeu M. V. M.
As an ecotoxicological test organism, Daphnia magna Straus has a long history and is now used extensively. Despite this, considerable variation in interlaboratory bioassays using the same reference toxicant has been reported. Using a standard quantitative genetics approach, the relative tolerance of different genotypes of Daphnia magna to two toxicants (sodium bromide and 3,4-dichloroaniline) was assessed. As expected, the environmental component of variability dominated the chronic response with a significant component of interaction. Differences between genotypes, although significant, were not large. It was concluded that genotype-environment interactions played a key role in determining chronic responses of Daphnia magna to both compounds. Some suggestions are given to improve the level of repeatability in Daphnia magna bioassays.